Redes e consumo solidário a experiência da rede xique xique em Mossoró –RN - Souza, Átalo da Silva (Universidade Federal Rural do Semi-Árido, 2021)
This work aimed to understand how the Rede Xique Xique promotes the culture of solidary consumption in Mossoró/RN, aiming to analyze the importance of the network as a community organization for promoting educational processes, understand and analyze the strategies for promoting solidary marketing, know the socioeconomic and political profile of producers and consumers related to the period of the COVID-19 pandemic. From a methodological point of view, we support dialectical-historical materialism as a method of understanding reality. A research has a qualitative and more exploratory approach, having as a data collection instrument the application of questionnaires with producers and consumers. As a theoretical framework, we take Singer (2002), Freire (1996), Gadotti (2009), Mance (2002), Gohn (2006) among others as the main basis for the discussion. The research results were emanated in light of the critical analysis of the discourse supported by the perspective of Norman Fairclough (2016). It is concluded that initiatives such as the Rede Xique Xique become viable as concrete organizational initiatives to strengthen farmers who collectively obtain better results in training, production, marketing, access to public policies, income generation and in a process of autonomy that involves the whole society in the discussion about solidary consumption through actions such as agroecological fairs, fixed commercial spaces, participation in institutional sales. We also reflect on the importance of this discussion for the training of teachers of rural education in a perspective of presenting alternatives that are imposed by capitalism
Keywords: Economia solidária; Redes de colaboração; Rede Xique Xique; Solidarity economy; Collaboration networks; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO RURAL